Weighted approximation in mean of classes of analytic functions by algebraic polynomials and finite-dimensional subspaces - Romanyuk, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish estimates for classic approximation quantities for sets from functional spaces (classes of functions analytic in Jordan domains), namely, for the best polynomial approximations and Kolmogorov widths.